AB0343 Myocardial involvement in patients with rheumatoid arthritis evaluated by two-dimensional speckle tracking echocardiography before and after 18 months of treatment with anti-tnf drugs. (12th June 2018) - Atzeni, F.; Gianturco, L.; Boccassini, L.; Sarzi-Puttini, P.; Turiel, M.
Abstract : Background: Cardiovascular (CV) mortality and morbidity is increased in rheumatoid arthritis (RA). Studies found a more than two- three-fold higher prevalence of ischaemic heart disease in RA patients compared to controls. However, a number of studies indicate that RA is also associated with various non-atherosclerotic CV manifestations. The inflammatory processes in RA may affect different structures of the heart: the most characteristic lesions are conduction defects, but other less frequent manifestations are pericarditis, cardiomyopathy and valve disease. Objectives: The aim of this study was to evaluate left ventricular myocardial function with two-dimensional speckle tracking echocardiography (STE), in addition to conventional Doppler and tissue Doppler echocardiography, in order to detect subclinical left ventricular myocardial dysfunction in patients with RA. Methods: The study involved 30 outpatients who fulfilled the 2010 ACR/EULAR) criteria for RA (11 males and 19 females; mean age 54.63±9.36 years, median disease duration 2 years), at baseline at after 18 months of treatment with anti-TNF drugs and 30 healthy controls matched in terms of age, gender and other anthropometric characteristics. All patients underwent a complete physical examination and routine laboratory analysis. CV risk profiles were assessed by means of standard ECG, conventional and stress trans-thoracic echocardography with the measurement of CFR, carotid ultrasonography and pulse wave velocity (PWV). Two-dimensional echocardiographic images were obtained using the apical 4-chamber view at a high frame rate of 70–80 frames/s, and three cardiac cycles were stored in cine-loop format for off-line analysis using commercially available QLAB 9 software (Philips Medical System, USA) in order to assess global longitudinal strain (GLS). Results: None of the patients showed any signs or symptoms of CV disease, pulmonary involvement, or any other complication. The results of the speckle tracking analysis were significantly different between the two groups, with GLS being significantly lower in the RA patients compared to healthy controls (GLS%: 18.51±9.63 vs 20.23±2.71; p<0.05). Right and left PWV (PWV right, m/sec: 7.52±1.64 vs 6.85±2.02; p=0.06 and PWV left, m/sec: 7.56±1.60 vs 6.88±2.11; p=0.07) and right and left coronary intima media thickness (cIMT) (cIMT right mm: 0.90±0.22 vs 0.75±0.13; p<0.05 and cIMT left, mm: median 0.89±0.18 vs 0.75±0.09; p<0.05) values were all higher in the RA patients and the differences of cIMT were statistically significant. Furthermore, a significant improvement in GLS in RA patients at 18 months of anti-TNF treatment was observed (GLS%: 18.51±9.63 vs 19.09±9.72 p <0.01). Conclusions: GLS measured by means of speckle tracking echocardiography was impaired in RA patients in the absence of any clinical evidence of CV disease and echocardiographic evaluations negative. This data suggests an early myocardial alteration. Reference: [1] Baktir AO, Sarli B, Cebicci MA, et al. Preclinical impairment of myocardial function in rheumatoid arthritis patients. Detection of myocardial strain by speckle tracking echocardiography. Herz2015;40(4):669–74. Disclosure of Interest: None declared